Kebijakan Ketahanan Pangan Pemerintah Daerah Kabupaten Lingga - Mendra Wijaya; Syafhendry; Naval Suci Ramawulan (Jayapangus Press, 2023)
The purpose of this research is to examine the potential issue of a global recession which has an impact on the potential for a food recession after the pandemic hit Indonesia. In order to make the discussion more focused, this study focuses on the policy and strategy efforts of the local government of Lingga Regency in terms of food security to overcome the food crisis. The research method uses a qualitative approach with research subjects selected using purposive sampling. The research results show that the local government's efforts to realize regional food security are realized by making regional policies to guarantee sustainable agricultural land so that land allotment is only for agriculture to prevent land conversion. This is also to realize agricultural development planning under the 2016-2021 Lingga Regency Regional Medium-Term Development Plan focusing on agricultural development with the Agrominapolitan program, which will continue in the following regional leadership. In the effort to regional food security, the contribution of the community, mainly subsistence farmers, has had a significant impact in supporting food supply for the Lingga district, which so far has been very dependent on food supplies from other regions, so that food shortages have become high, especially during specific climate changes.